2015
DOI: 10.1161/jaha.114.001733
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 Knockout Mouse Develops Spontaneous Atrial Fibrillation and Provides Mechanistic Insights Into Human Disease Process

Abstract: BackgroundAtrial fibrillation (AF) is a complex disease process, and the molecular mechanisms underlying initiation and progression of the disease are unclear. Consequently, AF has been difficult to model. In this study, we have presented a novel transgenic mouse model of AF that mimics human disease and characterized the mechanisms of atrial electroanatomical remodeling in the genesis of AF.Methods and ResultsCardiac‐specific liver kinase B1 (LKB1) knockout (KO) mice were generated, and 47% aged 4 weeks and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 55 publications
2
54
0
Order By: Relevance
“…Here we also found that the heart of KO mice appeared larger than that of the Lkb1 flox/flox mice. Consistently, cardiac-specific deletion of Lkb1 resulted in the hypertrophy and dysfunction of heart9 but did not affect the body weight78. Taken together, the reduction of body weight in the TMX-inducible Lkb1 knockout mice may be mainly driven by the Lkb1 deficiency in liver or endothelial cells, and the reduction of fat mass may be a secondary effect of altered systemic energy metabolism.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Here we also found that the heart of KO mice appeared larger than that of the Lkb1 flox/flox mice. Consistently, cardiac-specific deletion of Lkb1 resulted in the hypertrophy and dysfunction of heart9 but did not affect the body weight78. Taken together, the reduction of body weight in the TMX-inducible Lkb1 knockout mice may be mainly driven by the Lkb1 deficiency in liver or endothelial cells, and the reduction of fat mass may be a secondary effect of altered systemic energy metabolism.…”
Section: Discussionmentioning
confidence: 70%
“…Cardiac-specific deletion of Lkb1 causes early defects in atrial channel expression, atrial fibrillation, hypertrophy and heart dysfunction789. Liver-specific deletion of Lkb1 in mice results in defective canaliculi and bile duct formation, hyperglycemia, body weight reduction and death2101112.…”
mentioning
confidence: 99%
“…68 Moreover, cardiomyocyte-specific ablation of liver kinase B1, an activator of AMPK, in a mice model resulted in the development of spontaneous AF and an age-dependent progression of AF from a paroxysmal to a persistent form. 69 Collectively, these findings again suggest the importance of atrial metabolic remodeling in AF.…”
Section: Aging Increases Oxidative Stress and Inflammationmentioning
confidence: 84%
“…However, increased AMPK is traditionally considered a protective factor, improving metabolic disturbances and cellular dysfunction [9]. In agreement, recent work showed that knock-out of liver kinase B1, an activator of AMPK, reduces AMPK activation and results in an age-dependent development of spontaneous AF in mice [21]. Since the present work did not validate whether AMPK inhibition reduces apoptosis under these experimental conditions, AMPK activation might be an adaptive response to AF, with the apoptosis resulting from other pathways activated during AF.…”
mentioning
confidence: 81%